2018
DOI: 10.1080/15592294.2018.1526027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D depletion during development on mouse sperm DNA methylation

Abstract: Suboptimal environmental conditions during development can substantially alter the epigenome. Stable environmentally-induced changes to the germline epigenome, in particular, have important implications for the health of the next generation. We showed previously that developmental vitamin D depletion (DVD) resulted in loss of DNA methylation at several imprinted loci over two generations. Here, we assessed the impact of DVD on genome-wide methylation in mouse sperm in order to characterize the number, extent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In addition, maternal plasma levels of vitamin D along with ancestry affect DNA methylation in infants [219]. Murine models showed that vitamin D deficiency during pre-and postnatal development induces changes in the methylome that can persist throughout many generations [220,221]. More specifically, maternal vitamin D status, as well as gestational supplementation with this micronutrient, inversely correlate with perinatal DNA methylation at the retinoid X receptor alpha (RXRA) gene [222,223].…”
Section: Vitaminsmentioning
confidence: 99%
“…In addition, maternal plasma levels of vitamin D along with ancestry affect DNA methylation in infants [219]. Murine models showed that vitamin D deficiency during pre-and postnatal development induces changes in the methylome that can persist throughout many generations [220,221]. More specifically, maternal vitamin D status, as well as gestational supplementation with this micronutrient, inversely correlate with perinatal DNA methylation at the retinoid X receptor alpha (RXRA) gene [222,223].…”
Section: Vitaminsmentioning
confidence: 99%
“…The ZNF232 locus was associated with a family history of Alzheimer’s disease in a GWA meta-analysis [93]. The intergenic CpG on chromosome 4 (cg27284194) has been previously associated with infertility [94,95]. In GWASs, the region 4: 927973–1039876 (harboring mQTLs for cg27284194) has been associated with a number of traits and diseases, including bone mineral density [96,97,98,99,100] and several metabolomic characteristics such as blood protein [101,102] and triglyceride [103] levels (See Table S19).…”
Section: Resultsmentioning
confidence: 99%
“…Such paradoxical findings have also been reported in cancer models and suggest that the effects of folate levels on DNA methylation are site-specific rather than epigenome-wide [ 60 , 61 ]. While developmental vitamin D depletion has been generally associated with hypomethylation [ 62 , 63 ], these associations were locus-specific [ 44 ]. Our findings are the first to demonstrate an inverse relationship between developmental vitamin D levels and DNA methylation at MEs.…”
Section: Discussionmentioning
confidence: 99%